70.4k views
3 votes
4x - 3y = 6 ,7x + 3y =27


2 Answers

6 votes

Answer:

x=3 and y=2

Explanation:

Let's solve your system by substitution.

4x−3y=6;7x+3y=27

Step: Solve4x−3y=6for x:

4x−3y=6

4x−3y+3y=6+3y(Add 3y to both sides)

4x=3y+6

4x /4 = 3y+6 /4 (Divide both sides by 4)

x= 3 /4 y+ 3 /2

Step: Substitute

3 /4 y+ 3 /2 for x in7x+3y=27:

7x+3y=27

7( 3 /4 y+ 3 /2 )+3y=27

33 /4 y+ 21 /2

=27 (Simplify both sides of the equation)

33 /4 y+ 21 /2 + (−21 /2 )

=27+ (−21 /2) (Add (-21)/2 to both sides)

33 /4 y= 33 2

33/4y=33/2

33 /4 =33/4 (Divide both sides by 33/4)

y=2

Step: Substitute 2 for y in x= 3 /4 y+ 3 /2

x= 3 /4 y+ 3 /2

x= 3 /4 (2)+ 3 /2

x=3 (Simplify both sides of the equation)

Answer:

x=3 and y=2

HOPE THIS HELPS!!!! :)

<333333333333333

User Juan Ariza
by
5.3k points
6 votes

Answer:

Explanation:

4x - 3y = 6

7x + 3y = 27

11x = 33

x = 3

7(3) + 3y = 27

21 + 3y = 27

3y = 6

y = 2

(3,2)

User Smeegs
by
5.2k points